Antibiogram of clinical isolates from primary and secondary healthcare facilities: A step towards antimicrobial stewardship. - Isabel Naomi Aika; Ehijie Enato (Public Library of Science (PLoS), 2022)
Antibiogram development and use is a core element of antimicrobial stewardship practice, such data is scarce in healthcare settings in developing countries. The study aims to determine the epidemiology of clinical isolates and their antibiograms in secondary healthcare (SHC) and primary healthcare (PHC) facilities in Benin City, Nigeria. This was a retrospective study in three laboratories in SHC and PHC facilities. Microbial culture and susceptibility report over the past 4 years was collated. Ethical Clearance was obtained from the Edo State Ministry of Health and Benin City. Data were entered and analyzed using SPSS version 22. Of the 819 isolates, urine, semen and vagina swab were most represented (50.7%; 16.1%; 13.2%). S.aureus (60.6%) and coliform organism (31.9%) were commonly isolated. High resistance of 75%->90% was seen with penicillin, cephalosporin, macrolide, aminoglycoside and floroquinolone against S. aureus, Ps aeruginosa, coliform and E. coli. Resistance to all antimicrobials was observed in 11.7% of the isolates, multidrug resistance (MDR) was found to be 61.4%. MDR for Ps aeruginosa, coliform, E coli, and staph aureus were 95.5%, 67.3% 25.6% and 82.8% respectively. In the SHC, 15.4% of isolates were resistant to all antibacterial compared to none in the PHC. There was consistent yearly increase in resistance to more than six agents in both centers. Gender difference in antimicrobial resistance was observed. High MDR observed in this study emphasizes the need for routine antibiogram and its use in updating treatment guidelines to reflect the current resistance pattern to available antimicrobials.